Altered Perception of Facially Expressed Tiredness in Insomnia. (January 2018) - Akram, Umair; Sharman, Rachel; Newman, Amy
The present study compared normal sleepers and individuals displaying insomnia symptoms in their ratings for the expression intensity of tiredness and alertness whilst observing tired and neutral faces. Fifty-six normal sleepers and 58 individuals with insomnia symptoms observed 98 facial photographs (49 neutral, 49 tired). Using a visual analogue scale, participants were required to rate the extent to which each face appeared as tired and alert. Tired faces were created by manipulating neutral photographs to include previously identified facial tiredness cues. All participants rated sleep-related faces as more tired and less alert relative to neutral photographs. A significant Group × Face × Rating interaction demonstrated that, compared with normal sleepers, the insomnia symptoms group showed lower ratings for the expression of tiredness, but not alertness, whilst observing the tired faces. The findings suggest that the presence of insomnia symptoms is associated with reduced ratings of expression intensity for sleep-related facial photographs displaying tiredness. These outcomes add to the body of literature on how facial cues of tiredness are perceived by those with insomnia symptoms. Further work is required to elucidate the mechanisms underlying the relationship between insomnia symptoms and reduced perceptions of facially expressed tiredness.